Astrocytes Methods and Protocols - Milner, Richard.; Milner, Richard. (Methods in Molecular Biology, 2012)
Ever since their discovery more than 150 years ago, astrocytes have proved to be something of an enigma.  Only in the last 10-15 years has it become clear that astrocytes are multifunctional versatile cells that play key roles in a multitude of diverse processes in the CNS. Astrocytes: Methods and Protocols provides scientists with a comprehensive guide to many techniques used for astrocyte cell culture, as well as more specialized approaches for studying astrocyte functions, both in vitro and in vivo. Key cellular, molecular and biochemical techniques are used to study the many and varied functions of this fascinating cell.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.       Authoritative and practical Astrocytes: Methods and Protocols seeks to aid scientists and researchers looking to use more specialized techniques to examine astrocyte function. .